A wire-tap approach to enhance security in communication systems using the encoding-encryption paradigm - Mihaljevic, Miodrag (2010)
Motivated by the GSM system, we consider communication systems which employ the encoding-encryption paradigm of first encoding the data before encrypting it for transmission. We add one level of security to the existing system designs by introducing a wiretap encoder.We analyze the security from an information theoretical point of view, and prove the enhanced security of the proposed scheme, focusing on the case of known plain text attacks that can endanger not only the confidentiality of some messages but also the safety of the key used for encryption, and thus the security of the whole communication system.